2013
DOI: 10.1002/oby.20390
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and colorectal adenomatous polyps: A cross-sectional study in Korean adults

Abstract: Objective: This study aimed to examine the association between obesity and the risk of colorectal adenomatous polyps. Design and Methods: The design of this study is a cross-sectional study. A total of 1,574 participants (818 males and 756 females), who had undergone colonoscopy for health examinations at the National Cancer Center hospital in South Korea from February to September 2009, were included in the analysis. Results: The prevalence of colorectal adenomatous polyps was 39.5% in males and 22.6% in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…We also did not find an association between overweight and/or obese with the prevalence of colorectal adenomas in the current analysis. Differences between our study and these studies [20][21][22] include: (1) study settings where we performed a case-control study among individuals who underwent a colorectal screening program using iFOBT test and colonoscopy while these studies were among those who underwent the colonoscopy only, and (2) these studies [20][21][22] We found that underweight among male individuals were significant associated with colorectal adenomas prevalence in the current study, which is inconsistent with prior studies that overweight and/or obese increased risk of colorectal adenomas in both sexes in non-Asian populations. [13][14][15]25,26 This association was observed particularly among ethnically diverse population 26 and among obese but metabolically healthy individuals.…”
Section: Discussioncontrasting
confidence: 71%
“…We also did not find an association between overweight and/or obese with the prevalence of colorectal adenomas in the current analysis. Differences between our study and these studies [20][21][22] include: (1) study settings where we performed a case-control study among individuals who underwent a colorectal screening program using iFOBT test and colonoscopy while these studies were among those who underwent the colonoscopy only, and (2) these studies [20][21][22] We found that underweight among male individuals were significant associated with colorectal adenomas prevalence in the current study, which is inconsistent with prior studies that overweight and/or obese increased risk of colorectal adenomas in both sexes in non-Asian populations. [13][14][15]25,26 This association was observed particularly among ethnically diverse population 26 and among obese but metabolically healthy individuals.…”
Section: Discussioncontrasting
confidence: 71%
“…This obesity-related factor indicates that not only maintaining a normal BMI, but also keeping WC at ≤89.9 cm is important. Previous studies found that WC ≥90.0 cm increases the risk of polyp incidence by 1.59 times [30].…”
Section: Discussionmentioning
confidence: 90%
“…Obesity is a known risk factor for higher incidence of colorectal adenomas, advanced colorectal adenomas, and CRC. 2,3 Most studies assessing the influence of obesity on CRC, as well as on other diseases, employ body mass index (BMI) as an indicator of body fat and obesity. However, precise interconnections between BMI and CRC are still vague.…”
Section: Introductionmentioning
confidence: 99%